Relations between harsh discipline from teachers, perceived teacher support, and bullying victimization among high school students - Banzon-Librojo, Lorelie Ann (Archīum Ateneo, 2017)
This study examined how the experience of harsh discipline from teachers is related to students' experience of bullying victimization in a Philippine high school. Respondents were 401 first- to fourth-year high school students of an urban public school in the Philippines. Using structural equation modeling, a hypothesized model with direct associations between harsh discipline and bullying victimization, and an indirect path via students' perception of teacher support, was tested. The data adequately fit the model and showed that experiences of harsh teacher discipline predicted higher bullying victimization and students' negative perception of teacher support. There were no significant indirect effects. The findings suggest that school discipline strategies may have repercussions on students' behaviors and relationships, highlighting the teacher's role in modeling and setting norms for acceptable behaviors. Future studies can examine further how teachers' harsh or positive discipline behaviors relate to bullying.